INVESTIGATING TEACHERS’ BELIEF AND PRACTICES TOWARD DIGITAL MEDIA OF ENGLISH LEARNING DURING COVID-19 PANDEMIC - Berlinda Mandasari; Dyah Aminatun (English Review: Journal of English Education, 2022)
The advancement of technology has made a lot of changes especially in educational field. Online learning is one of teaching modes as the response to the educational changes. Moreover, during Covid-19 pandemic, online learning is not an alternative solution, but a compulsory one. In response to this, various kinds of online learning media do exist to use. This study aimed at exploring teachers’ beliefs toward digital media of English learning during Covid-19 pandemic. This study uses qualitative design with participants coming from teachers teaching English at vocational school. Observation and semi-structured interview are used to gain data about teachers’ beliefs. Data were collected and analyzed by descriptively. The result of this research shows that Google Classroom, Instagram, and WhatsApp are preferable for conducting online learning. It shows the common digital media are preferred used by the teachers in order to enable the students to easily engage in the English learning process since the media are reachable and easy to access.